PHILIPINES POLICY OF WAR ON DRUGS UNDER INTERNATIONAL LAW - Adan, Aroon; Bituin, Ariana; Darian, Jane (Universitas Nasional, 2023)
This study aims to explain what human rights violations occurred in the War on Drugs Policy in the Philippines and the response given by the international community. The method used in this research is the qualitative method. This research is motivated by the Philippines' policy to eradicate drugs in a massive way that causes human rights violations. In this study, the theory used is Human Rights and International Law. The results of this study found that human rights violations committed by the Philippines have violated international human rights law as regulated in the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). In addition, more special efforts are needed from the United Nations (UN) and the International Criminal Court (ICC) in stopping human rights violations that occur in the Philippines.